(untitled) (JURNAL DURA NEGARA, 2026)
The COVID-19 pandemic caused unprecedented disruption to the global aviation industry, including in Indonesia, necessitating adaptive national policies aligned with international safety standards. This article analyzes the role of the International Civil Aviation Organization (ICAO) in shaping Indonesia’s aviation policies during the pandemic, particularly through the adoption of Minister of Transportation Circular Letters No. 13 of 2020 and No. 10 of 2021. Using a qualitative approach and historical method, the study employs institutional liberalism and international regime theory to explain how global norms influence domestic decision-making. The findings indicate that Indonesia integrated ICAO recommendations—especially health protocols and operational guidelines issued by the Council Aviation Recovery Task Force (CART)—into national regulations. This integration strengthened policy consistency, enhanced public trust, and ensured the continuity of air transport services during the global health emergency. The study underscores the importance of international institutions in maintaining governance stability during crises and demonstrates how global standards can reinforce national resilience in the aviation sector.